THE IMPACT OF INTRODUCING THE CHINESE LANGUAGE PROGRAM FOR EMPLOYABILITY IMPROVEMENT IN CAMBODIA - Zheng Wei; Dr. Paradise Ros (JF Publisher, 2024)
Chinese language program is as important as English language program in Cambodia for employability improvement. However, some universities in Cambodia have not yet created the program for their students due to political controversy. This study aims to thoroughly investigate the impact of Chinese proficiency on employment capabilities in Cambodia. Through surveys and data analysis of Cambodian participants, we systematically examined the role of Chinese proficiency in the job market. Qualitative research method has been used in order to interview and survey 200 participants for exploring the salary and expected income after Chinese language acquisition in firms. Using a nonprobability sampling approach for current research participants to find potential new subjects from their social network. The survey results indicate that a majority of participants believe that mastering Chinese can bring additional income in the workplace, with some expressing that learning Chinese can significantly increase their salary. However, from the perspective of employers, Chinese proficiency is not a direct prerequisite for salary increments but serves as an important screening criterion in the hiring process. The research explores the impact of Chinese language proficiency on salaries and career development in Cambodia. It suggests that improving listening and character writing skills is challenging, but employers value Chinese proficiency in communication. To improve Chinese proficiency, schools should focus on comprehensive language skills, align instructional content with job requirements, and provide practical experience.